Serotyping and Antimicrobial Resistance Profiling of Multidrug-Resistant Non-Typhoidal Salmonella from Farm Animals in Hunan, China - Zhuohui Zhang; Jiyun Li; Rushun Zhou; Qianqian Xu; Shiyin Qu; Hongguang Lin; Yan Wang; Pishun Li; Xiaofeng Zheng (MDPI AG, 2023)
Non-typhoidal Salmonella (NTS) is a foodborne pathogen and a prevalent causative agent for disease outbreaks globally. The Salmonella enterica serovar 4,[5],12:i:- (S.4,[5],12:i:-) belongs to the monophasic variant of Salmonella typhimurium, which is of current global concern. In this study, the epidemiology and genomic characterization of S. 4,[5],12:i:- isolates from 17 livestock farms in Hunan Province between 2019 and 2020, as well as their susceptibility to 14 antimicrobial agents, were profiled. Twelve Salmonella serotypes were identified using the White-Kauffmann-Le Minor scheme, and whole-genome sequencing analyses were conducted based on these isolates. Overall, 107 Salmonella strains were isolated, of which 73% (78/107) were multidrug resistant. Resistance to tetracycline (85.05%) was found to be the most prevalent, followed by the oqxAB and aac(6')-Ib-cr genes. S. typhimurium (monophasic) 4,[5],12:i:- was the most common serotype, followed by S. typhimurium and S. derby. Most antimicrobial-resistant strains were isolated from pigs, indicating that they could be important reservoirs of resistant non-typhoidal Salmonella strains. The presence of similar genetic environments in S. 4,[5],12:i:- indicates both vertical and horizontal transmission of resistance plasmids, which may promote the spread of drug resistance genes. Appropriate measures should be taken to curb the prevalence of S. 4,[5],12:i:-.